La Ética y la Responsabilidad Social Empresarial, un reto para las Empresas en preservar los recursos naturales del Ecuador - López-Pérez, Patricio Javier (Editorial Grupo AEA, 2022)
The organizations demonstrate an adequate conduct based on their organizational culture, which facilitates decision making as well as contracting a good relationship internally and externally, and even being able to apply a good Corporate Social Responsibility (CSR) with society and its environment. This research aims to determine the impact that ethics and CSR have had in the search to contribute to the preservation of natural resources in Ecuador through social, economic and environmental improvements assumed by socially responsible entities. Therefore, it is based on a documentary and bibliographic methodology by using bibliographic sources, books, journals, scientific articles to have a base supported by the information collected to make a response to the main theme. The results show an increase in the level of interest of the population in issues that affect the environment and generate pollution, while the discussion shows that for Ecuadorian companies, concepts such as CSR are relatively new, causing organizations to overlook the creation of policies for the ethical care of natural resources. This leads to the conclusion that in Ecuador there is evidence of a growth in organizations focused on CSR because of the existence of many companies that do not apply practices to preserve sustainable development, due to the need to avoid expenses and prioritize their income over the environment.